L’école de Paris et l’archéologie classique en Allemagne - Nikolaus Dietrich (Cahiers Mondes Anciens)
This paper analyses the reception of the researches of the “Paris school” in the context of the German “Klassiche Archäologie” which, more or less at the same moment, was also entering a period of renewal aiming at a conjunction of history and archaeology. Despite the initial enthusiasm, this reception was only partial. Indeed, the rethinking of the classical disciplines in France and Germany took diverging roads because of both the different respective traditions under discussion and their different goals. One can identify four major differences between the two projects: (1) the “Greek art” pays a much more dominant part in the “Klassiche Archäologie” than in the Greek archaeology in France; (2) Greek religion is at the heart of the anthropological approach of the “Paris school” while it is marginalized in the German classical archaeology; (3) political history is essential to the conjunction of history and archaeology in Germany, while the “Paris school” conceptualizes history in a different way, overlooking factual history and micro-chronology; (4) the utopian dimension of the Greek past, that the “Klassiche Archäologie” rejected though it was deeply rooted in his own tradition, while some kind of utopia was still operating in the “Paris school” whose researches put the emphasis on the alterity of a premodern society, freed from any normative value for the present time, and functioning rather as a critical discourse addressing the contemporary culture.